Academic literacy across the curriculum: Towards a collaborative instructional approach. (19th October 2016) - Wingate, Ursula
Abstract : I respond to the conference theme 'English across the Curriculum' by suggesting that 'Academic literacy' should be taught across the curriculum. I first explain the concept of academic literacy, which describes the range of abilities that students have to acquire when starting out in a new academic discipline. I then discuss the dominant instructional provision at universities. As this provision fails to address students' real learning needs, I argue for curriculum-integrated academic literacy instruction that is based on the collaboration between English for academic purposes (EAP) specialists and subject lecturers. I provide examples of collaborative, discipline-specific approaches to supporting student learning, and present some insights from an intervention study that I have carried out to explore feasible ways of teaching and collaboration. Finally, I discuss the need for lecturer training to achieve a curriculum-integrated approach, and report on my experience of running a professional development module which aimed to enable lecturers to embed academic literacy development into their teaching practice.